New frontiers: an enriched perspective on extraction frontiers in Indonesia. Issue 3 (3rd July 2017) - de Jong, Edwin B. P.; Knippenberg, Luuk; Bakker, Laurens
ABSTRACT: Changes in the nature, scale, and speed of natural resource extraction, especially in the last two decades, have resulted in many new resource extraction areas emerging across the world. By zooming in on Indonesia, this article shows that the underlying causes and consequences of current trends are more complex than portrayed by the rancher-squatter model of frontiers that is still frequently used to explain these developments. We argue that a broadened frontier notion is necessary to address the multifaceted nature of the processes underway in contemporary Indonesian extraction areas, as well as beyond. We propose a perspective that pays explicit attention to four new developments that can be described by using the hybridization of space, time, actors, and rules, and are characterized by the fact that these processes create new perimeters in all four mentioned areas. In so doing, we challenge, broaden, and renew the meaning of frontiers.